Global trends in research of immune cells associated with hypertensive disorders of pregnancy: A 20-year bibliometric analyses (from 2001 to 2021) - Wang, Yue; Li, Baoxuan; Tong, Fei (Frontiers in Immunology, 2023)
Background: A growing evidence suggests that immune cells play a significant role in the pathogenesis of hypertensive disorders of pregnancy (HDP).Over the past 20 years, several studies have been conducted on the role of immune cells in hypertensive disorders of pregnancy. This study used bibliometric analysis to assess research hotspots and future trends in studies on immune cells in hypertensive disorders of pregnancy. Methods: We extracted all relevant literature on immune cells and hypertensive disorders of pregnancy from the Web of Science core collection for the period of 2001 to 2021. We used VOS Viewer, CiteSpace, R-bibliometrix and Python for bibliometric analysis. Results: We identified 2,388 records published in 593 journals by 9,886 authors from 2,174 universities/institutions in 91 countries/regions. The number of publications tended to increase over time, with the highest number of publications in 2021, up to 205. The USA was the country with the most publications. UNIVERSITY OF MISSISSIPPI was the most influential institution. Lamarca B, Romero R, and Saito S were the most prolific authors. Finally, three research hotspot clusters were identified based on keywords, which reflected the role of immune cells in the development of hypertensive disorders of pregnancy, the current research status,and predicted hot spots for future research. Conclusions: Our study systematically analyzed the role of immune cells in the pathogenesis of hypertensive disorders of pregnancy in the last 20 years. Our results indicated that immune cells, such as regulatory T cells, natural killer (NK) cells,and macrophages, and the cytokines released such as TNF-α, IFN-γ in the maternal circulation and at the maternal-fetal interface would influence the development of hypertensive disorders of pregnancy and we need further investigate the role of individual immune cells and translational studies to provide new therapeutic perspectives to mitigate adverse perinatal outcomes due to hypertensive disorders of pregnancy. In conclusion, bibliometric studies provide a general overview of immune cells in the study of hypertensive disorders of pregnancy.